Endolymphatic Sac Tumor Showing Increased Activity on 68Ga DOTATATE PET/CT. (October 2016) - Papadakis, Georgios Z.; Millo, Corina; Sadowski, Samira M.; Bagci, Ulas; Patronas, Nicholas J.
Abstract : Abstract: Endolymphatic sac tumors (ELSTs) are rare tumors arising from the epithelium of the endolymphatic sac and duct that can be either sporadic or associated with von Hippel-Lindau (VHL) disease. We report a case of a VHL patient with histologically proven residual ELST who underwent 68 Ga DOTATATE PET/CT showing increased activity (SUVmax, 6.29) by the ELST. The presented case of a VHL-associated ELST with increased 68 Ga DOTATATE uptake indicates cell-surface expression of somatostatin receptors by this tumor, suggesting the potential application of somatostatin receptor imaging using 68 Ga DOTA-conjugated peptides in the workup and management of these patients.